Improvement Gepler viscousimetr for research of the liquids with high optical density and viscosity - А. А. Smirnykh (Тонкие химические технологии)
Addition of Gepler viscousimetr (VN-II) the new original constructive elements allow enlarge the interval of possible application for research of the liquids with high optical density and viscosity. The advanced construction of the device allows to increase accuracy of received results of measurements.